The Gal/GalNac lectin as a possible acetylcholine receptor in Entamoeba histolytica - Pacheco-Sánchez, Marisol; Martínez-Hernández, Sandra Luz; Muñoz-Ortega, Martín Humberto; Reyes-Martínez, Jesús Alejandro; Ávila-Blanco, Manuel Enrique; Ventura-Juárez, Javier (Frontiers in Cellular and Infection Microbiology, 2023)
Entamoeba histolytica (E. histolytica) is a protozoan responsible for intestinal amebiasis in at least 500 million people per year, although only 10% of those infected show severe symptoms. It is known that E. histolytica captures molecules released during the host immune response through membrane receptors that favor its pathogenetic mechanisms for the establishment of amebic invasion. It has been suggested that E. histolytica interacts with acetylcholine (ACh) through its membrane. This promotes the increase of virulence factors and diverse mechanisms carried out by the amoeba to produce damage. The aim of this study is to identify a membrane receptor in E. histolytica trophozoites for ACh. Methods included identification by colocalization for the ACh and Gal/GalNAc lectin binding site by immunofluorescence, western blot, bioinformatic analysis, and quantification of the relative expression of Ras 5 and Rab 7 GTPases by RT-qPCR. Results show that the Gal/GalNAc lectin acts as a possible binding site for ACh and this binding may occur through the 150 kDa intermediate subunit. At the same time, this interaction activates the GTPases, Ras, and Rab, which are involved in the proliferation, and reorganization of the amoebic cytoskeleton and vesicular trafficking. In conclusion, ACh is captured by the parasite, and the interaction promotes the activation of signaling pathways involved in pathogenicity mechanisms, contributing to disease and the establishment of invasive amebiasis.